Contemporary macroeconomics - Bose, Amitrya (Ed.); Ray, Debraj (Ed.); Sarkar, Abhirup (Ed.) (New Delhi Oxford University Press, 2001)
This book covers topics of contemporary relevance to student s and researchers of economic including conceptual and applied aspects of national income accounting.Macroeconomics constraints faced by developing economics,modern growth theory,finance and ins
Keywords: Macroeconomics; Economics-India